2023
DOI: 10.1007/s11259-023-10121-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant proteins including the B-cell epitopes of autolysin A of Staphylococcus aureus isolated from clinical sheep mastitis and their potential for vaccine development

Abstract: Staphylococcus aureus is the most common clinical mastitis-associated pathogen in sheep which contributes to reduced welfare of affected animals and, therefore, compromises the quality and quantity of milk production. To prevent mastitis and its spread, it is essential to guarantee adequate breeding conditions and animal health, through the adoption of good farm management practices and the application of suitable biosecurity measures. Vaccination can play a strategic role in prevention, control, and eradicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Staphylococcus aureus causes multifarious infections in human and animal health, including in human‐related pneumonia, endocarditis, and mastitis in sheep and bovine 1–4 . Over the years, because clinical research have manifested that the vaccine is the most effective strategy in treating S. aureus infection, it is very necessary to develop an effective vaccine against S. aureus , 5–8 however, there is currently a lack of effective vaccine against S. aureus in the market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus causes multifarious infections in human and animal health, including in human‐related pneumonia, endocarditis, and mastitis in sheep and bovine 1–4 . Over the years, because clinical research have manifested that the vaccine is the most effective strategy in treating S. aureus infection, it is very necessary to develop an effective vaccine against S. aureus , 5–8 however, there is currently a lack of effective vaccine against S. aureus in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus causes multifarious infections in human and animal health, including in human‐related pneumonia, endocarditis, and mastitis in sheep and bovine. 1 , 2 , 3 , 4 Over the years, because clinical research have manifested that the vaccine is the most effective strategy in treating S. aureus infection, it is very necessary to develop an effective vaccine against S. aureus , 5 , 6 , 7 , 8 however, there is currently a lack of effective vaccine against S. aureus in the market. Our previous research showed that IsdB 137‐361 of the iron surface determinant B protein (IsdB) from S. aureus triggers a strong immune response in animal, but its immunoprotective effect is still to be further promoted.…”
Section: Introductionmentioning
confidence: 99%